(3GdWH GdfaSj aj GdMVGQI GdESdGejIs (3JfXjQ hJCSjS hEHOGYs - (3MQHj, NGdOs ((3GdbGgQIs (3GdecJH GdLGeYj GdMOjKs, 2011)
(3ajeG jNU GdWH GdfaSj, aEf GdJbdjH hGdJaJjT hGdJeMjU hGdOQGSI aj GdeNWhWGJ GdYQHjI GdESdGejI heMGhdI agegG hJMbjbgG djhVM HUhQI LdjI Cf eNWhWGJ MVGQJfG GdYQHjI GdESdGejI eGRGdJ JMhi cfhRkG hPNGFQkG de jcTa YfgG HUhQI dGFbI MJi Gdjhe?(B. (3hef Hjf gPg GdPNGFQ hJdc GdcfhR, Ydhe HCcedgG, CHOYgG GdYbd GdYQHj GdESdGej, hde Jfd fUjHgG GdhGaj ef GdcTa hGdHjGf hGdJHjjf hGdOQGSI, NGUI hEf efgG YdhekG eGRGdJ aGYdI MJi Gdjhe, hef Cge gPg GdYdhe, hCcKQgG aGYdjI MJi gPg GddMXI, GdWH GdfaSj GdJWHjbj, Ch eG jecf JSejJg (B"(3Yde GdfaS GdYQHj GdESdGej(B"(3, GdPj jYO GHJcGQkG YQHjkG ESdGejkG NGdUkG HGYJQGa GdZQHjjfs
Keywords: (3GdESdGe hGdWH GdfaSjs; (3GdMVGQI GdESdGejIs